Exploring written narrative in children with poor reading comprehension - Cragg, L; Nation, K (2006)
This study investigated written language production in 10yearold children with impaired reading comprehension. Despite fluent and accurate reading, these children are poor at understanding what they read. Participants completed a spelling test, and were asked to write an extended narrative, prompted by a series of pictures. Poor comprehenders showed ageappropriate spelling skills, and their narratives did not differ from those produced by control children in terms of length or syntactic complexity. However, their narratives captured less of the story content, and contained a less sophisticated story structure. These findings are discussed within a framework that sees weaknesses in aspects of oral language placing constraints on aspects of written language production.